Salvage Magnetic Resonance Imaging–guided Transurethral Ultrasound Ablation for Localized Radiorecurrent Prostate Cancer: 12-Month Functional and Oncological Results - Mikael Anttinen; Pietari Mäkelä; Antti Viitala; Pertti Nurminen; Visa Suomi; Teija Sainio; Jani Saunavaara; Pekka Taimen; Roberto Blanco Sequeiros; Peter J. Boström (Netherlands, 2022)
Background
Up to half of all men who undergo primary radiotherapy for localized prostate cancer (PCa) experience local recurrence.
Objective
To evaluate the safety and early functional and oncological outcomes of salvage magnetic resonance imaging–guided transurethral ultrasound ablation (sTULSA) for men with localized radiorecurrent PCa.
Design, setting, and participants
This prospective, single-center phase 1 study (NCT03350529) enrolled men with biopsy-proven localized PCa recurrence after radiotherapy. Multiparametric magnetic resonance imaging (mpMRI) and 18F prostate-specific membrane antigen-1007 (18F PSMA-1007) positron emission tomography (PET)-computed tomography (CT) were used to confirm organ-confined disease localization. Patients underwent either whole-gland or partial sTULSA, depending on their individual tumor characteristics.
Outcome measurements and statistical analysis
Patients were followed at 3-mo intervals. Adverse events (AEs, Clavien-Dindo scale), functional status questionnaires (Expanded Prostate Cancer Index [EPIC]-26, International Prostate Symptom Score, International Index of Erectile Function-5), uroflowmetry, and prostate-specific antigen (PSA) were assessed at every visit. Disease control was assessed at 1 yr using mpMRI and 18F-PSMA-1007 PET-CT, followed by prostate biopsies.
Results and limitations
Eleven patients (median age 69 yr, interquartile range [IQR] 68–74) underwent sTULSA (3 whole-gland, 8 partial sTULSA) and have completed 12-mo follow-up. Median PSA was 7.6 ng/ml (IQR 4.9–10) and the median time from initial PCa diagnosis to sTULSA was 11 yr (IQR 9.5–13). One grade 3 and three grade 2 AEs were reported, related to urinary retention and infection. Patients reported a modest degradation in functional status, most significantly a 20% decline in the EPIC-26 irritative/obstructive domain at 12 mo. A decline in maximum flow rate (24%) was also observed. At 1 yr, 10/11 patients were free of any PCa in the targeted ablation zone, with two out-of-field recurrences. Limitations include the nonrandomized design, limited sample size, and short-term oncological outcomes.
Conclusions
sTULSA appears to be safe and feasible for ablation of radiorecurrent PCa, offering encouraging preliminary oncological control.
Patient summary
We present safety and 1-yr functional and oncological outcomes of magnetic resonance imaging–guided transurethral ultrasound ablation (TULSA) as a salvage treatment for local prostate cancer recurrence after primary radiation. Salvage TULSA is safe and shows the ability to effectively ablate prostate cancer recurrence, with acceptable toxicity.